42nd Winter School on Vibroacoustical Hazards Suppressions - Roman BUKOWSKI (Archives of Acoustics)
Traditionally, the 42nd Winter School on Vibroacoustical Hazards Suppressions national conference is organized by Upper Silesian Division of the Polish Acoustical Society. The conference again is organized in Szczyrk.